Independent and parallel evolution of new genes by gene duplication in two origins of C4 photosynthesis provides new insight into the mechanism of phloem loading in C4 species. - Kelly, S; Emms, D; Covshoff, S; Hibberd, J (Oxford University Press, 2016)
C4 photosynthesis is considered one of the most remarkable examples of evolutionary convergence in eukaryotes. However, it is unknown whether the evolution of C4 photosynthesis required the evolution of new genes. Genomewide gene-tree species-tree reconciliation of seven monocot species that span two origins of C4 photosynthesis revealed that there was significant parallelism in the duplication and retention of genes coincident with the evolution of C4 photosynthesis in these lineages. Specifically, 21 orthologous genes were duplicated and retained independently in parallel at both C4 origins. Analysis of this gene cohort revealed that the set of parallel duplicated and retained genes is enriched for genes that are preferentially expressed in bundle sheath cells, the cell type in which photosynthesis was activated during C4 evolution. Furthermore, functional analysis of the cohort of parallel duplicated genes identified SWEET-13 as a potential key transporter in the evolution of C4 photosynthesis in grasses, and provides new insight into the mechanism of phloem loading in these C4 species.